2019
DOI: 10.32604/biocell.2019.08177
|View full text |Cite
|
Sign up to set email alerts
|

Association of TRIM22 with the type 1 interferon response during primary human cytomegalovirus infection in THP-1 macrophages

Abstract: As a response factor of interferon, tripartite motif (TRIM) 22 was reported to exert antiviral activity against viruses. In this study, THP-1 macrophages were infected with human cytomegalovirus (HCMV) to establish the HCMV lytic infection model. The mRNA levels of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α) and interferonbeta (IFN-β) were significantly up-regulated in THP-1 macrophages at different infection time and titers. Moreover, for the first time, upregulation of TRIM22 expression was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In adipose tissue, inflammation inhibits adipocyte expansion and differentiation, alters adipocyte endocrine secretion, and induces extracellular matrix remodelling (Khan et al, 2009). Macrophages play an important role in chronic low-grade inflammation (Hong et al, 2020;Li et al, 2019;Lima et al, 2018). During the development of PCOS, it has been found that hyperandrogenic conditions may lead to the recruitment macrophages under the influence of chemokines (Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue, inflammation inhibits adipocyte expansion and differentiation, alters adipocyte endocrine secretion, and induces extracellular matrix remodelling (Khan et al, 2009). Macrophages play an important role in chronic low-grade inflammation (Hong et al, 2020;Li et al, 2019;Lima et al, 2018). During the development of PCOS, it has been found that hyperandrogenic conditions may lead to the recruitment macrophages under the influence of chemokines (Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%